2005
DOI: 10.1186/bf03351886
|View full text |Cite
|
Sign up to set email alerts
|

A synoptic study of VLF sudden phase anomalies recorded at Visakhapatnam

Abstract: A synoptic survey of Sudden Phase Anomalies (SPAs) observed in the phase variation measurements of 16 kHz VLF transmissions from Rugby (England) made at Visakhapatnam (India) has been carried out. These Sudden Ionospheric Disturbances caused during solar flares are examined in relation to flare time enhancements of X-ray radiation fluxes. It is found that nearly 81% of SPAs recorded have accompanying X-ray enhancements and in 80% of the cases H α flares and microwave bursts also occur concurrently. Using SPA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Wait (1959) and several authors made use of it, e.g. Kamada (1985), Khan et al (2005). For a waveguide in 1st mode approximation, for small λ/ h and small h he found a relation for the relative phase velocity decrease with decreasing reflection height from which, because of…”
Section: Propagation Calculations and Modeling Resultsmentioning
confidence: 99%
“…Wait (1959) and several authors made use of it, e.g. Kamada (1985), Khan et al (2005). For a waveguide in 1st mode approximation, for small λ/ h and small h he found a relation for the relative phase velocity decrease with decreasing reflection height from which, because of…”
Section: Propagation Calculations and Modeling Resultsmentioning
confidence: 99%
“…However, most of the reports on extraterrestrial radiation effect on the ionospheric D-region are originated in solar flares. During these flares, X-ray flux received at the Earth strongly intensifies within a few minutes and decays in up to several hours, while strongly affecting ionization processes in the ionosphere [e.g., Mitra and Rowe, 1972;Hunsucker and Hargreaves, 2002;Khan et al, 2005;Clilverd et al, 2009].…”
Section: Space Weather Phenomena and Eclipsesmentioning
confidence: 99%
“…Nevertheless, several studies were made in order to find X-ray flux thresholds needed for the generation of a VLF NB SPA [e.g., Kaufmann and de Barros, 1969;Muraoka et al, 1977;Pant, 1993;Khan et al, 2005]. Similarly, Kaufmann et al [2002] studied numerous solar flare events that did not produce SPAs.…”
Section: Space Weather Phenomena and Eclipsesmentioning
confidence: 99%
“…The majority of these studies reported the correlation between the logarithmic of the solar X‐ray peak flux (W/m 2 ) of the flare and the subsequent ionospheric disturbance observed as VLF anomalies. From this correlation it is possible to estimate the smallest solar X‐ray flare event that disturbed the daytime lower ionosphere conductivity enough to perturb the propagation of VLF waves (Kaufmann & Paes de Barros, ; Khan et al, ; Muraoka et al, ; Pant, ; Raulin et al, ). This minimal detected event suggests how sensitive the lower ionosphere is to solar flares; however, more understanding on this notion is needed.…”
Section: Introductionmentioning
confidence: 99%